2022
DOI: 10.1186/s13023-022-02366-x
|View full text |Cite
|
Sign up to set email alerts
|

Real-world clinicopathological features and outcome of thymic neuroendocrine tumors: a retrospective single-institution analysis

Abstract: Background Thymic neuroendocrine tumors comprise a heterogeneous group of rare diseases. This study aimed to investigate the real-world clinicopathological features and treatment outcomes of thymic neuroendocrine tumors. Results A total of 104 patients diagnosed with thymic neuroendocrine tumors in a single institution from 1983 to 2021 were eligible. Fourteen (13.46%) and 28 (26.92%) patients diagnosed with thymic neuroendocrine tumors suffered fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Compared with RFA of other parenchymal organs, the gas around the lung lesion can restrict the heat conduction during the ablation process, and the energy can be more easily gathered inside the lesion, which makes the ablation more efficient and effective; (5) When a biopsy is required, the biopsy needle and RF probe can be placed at the same time to avoid secondary puncture injury, and the small blood vessels damaged by the puncture cut can be closed with RF ablation heating to reduce the risk of bleeding. (6) Radiofrequency ablation as a local minimally invasive ablation treatment, combined with other therapeutic methods sometimes can improve the efficacy, such as radiotherapy, holistic therapy (depending on genetic test results, choose to use chemotherapy or molecularly targeted drug therapy) and so on.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with RFA of other parenchymal organs, the gas around the lung lesion can restrict the heat conduction during the ablation process, and the energy can be more easily gathered inside the lesion, which makes the ablation more efficient and effective; (5) When a biopsy is required, the biopsy needle and RF probe can be placed at the same time to avoid secondary puncture injury, and the small blood vessels damaged by the puncture cut can be closed with RF ablation heating to reduce the risk of bleeding. (6) Radiofrequency ablation as a local minimally invasive ablation treatment, combined with other therapeutic methods sometimes can improve the efficacy, such as radiotherapy, holistic therapy (depending on genetic test results, choose to use chemotherapy or molecularly targeted drug therapy) and so on.…”
Section: Discussionmentioning
confidence: 99%
“…In patients who are clinically diagnosed with Cushing's syndrome in combination with laboratory tests, hormone experiments and the evident ectopic ACTH lesions after imaging, conventional treatments such as drug therapy and surgical resection are challenging to implement (5,6). Some techniques can be used to target the lesions and control systemic symptoms,such as radiotherapy, chemotherapy, and radionuclides (5).…”
Section: Introductionmentioning
confidence: 99%
“…Thymic (5). And in June 2022, Chen et al reported their retrospective analysis of a remarkable 104 cases in a single center (6).…”
Section: Editorialmentioning
confidence: 99%
“…We would like to add two surgical papers to the discussion: Wang et al in 2016 published 18 t-NEN cases in this journal ( 5 ). And in June 2022, Chen et al reported their retrospective analysis of a remarkable 104 cases in a single center ( 6 ).…”
mentioning
confidence: 99%
“…Tumor size [ 7 ] and histopathologic subtype [ 8 ] are reported as prognostic factors. Although lymph nodes and distant metastases appear with high probability, the efficacy of chemotherapy or radiotherapy is reported to be insufficient for NETTs, and complete resection is important [ 3 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. The prognosis has become poor in the progressive stage, but this can be explained by the confounding effect of the possibility of complete resection [ 10 ].…”
Section: Introductionmentioning
confidence: 99%